Psychoanalytic approaches to myth : Freud and the Freudians - Merkur, Daniel (New York : Routledge, 2005)
The book surveys and evaluates the methods that Freud and the various psychoanalytic schools have employed in their studies of myths. In addition to providing a historical survey, the author argues that modern views of myth as something to be deplored because it is inconsistent with history and science depends on a misunderstanding of the nature of myth. Myth is not a product of unconscious irrationality but is instead a sustained use of metaphor. It expresses ideas in concrete imagery of unconscious inspiration, but the ideas can be rational and profound, as is also the case with poetry and s.
BOOK COVER; TITLE; COPYRIGHT; TABLE OF CONTENTS; Chapter 1 Mythology into Metapsychology; Chapter 2 Myth as Unconscious Manifestation; Chapter 3 Myth and the Basic Dream; Chapter 4 Myth as Defense and Adaptation; Chapter 5 Myth as Metaphor; Chapter 6 Therapeutic Insights in Myth; Epilogue Clinical Implications; References; Index.
Includes bibliographical references (pages 141-156) and index.
Print version record.
Keywords: Myth -- Psychological aspects; Mythology; Myth -- Psychological aspects; Mythology; PSYCHOLOGY -- Movements -- Psychoanalysis; Myth -- Psychological aspects; Myth -- Psychological aspects; Mythology; Electronic books